Parent-of-origin-dependent nucleosome organization correlates with genomic imprinting in maize - Dong, Xiaomei; Chen, Jian; Li, Tong; Li, En; Zhang, Xiangbo; Zhang, Mei; Song, Weibin; Zhao, Haiming; Lai, Jinsheng (Genome Research, 2018)
Genomic imprinting refers to allele-specific expression of genes depending on their parental origin. Nucleosomes, the fundamental units of chromatin, play a critical role in gene transcriptional regulation. However, it remains unknown whether differential nucleosome organization is related to the allele-specific expression of imprinted genes. Here, we generated a genome-wide map of allele-specific nucleosome occupancy in maize endosperm and presented an integrated analysis of its relationship with parent-of-origin-dependent gene expression and DNA methylation. We found that ∼2.3% of nucleosomes showed significant parental bias in maize endosperm. The parent-of-origin-dependent nucleosomes mostly exist as single isolated nucleosomes. Parent-of-origin-dependent nucleosomes were significantly associated with the allele-specific expression of imprinted genes, with nucleosomes positioned preferentially in the promoter of nonexpressed alleles of imprinted genes. Furthermore, we found that most of the paternal specifically positioned nucleosomes (pat-nucleosomes) were associated with parent-of-origin-dependent differential methylated regions, suggesting a functional link between the maternal demethylation and the occurrence of pat-nucleosome. Maternal specifically positioned nucleosomes (mat-nucleosomes) were independent of allele-specific DNA methylation but seem to be associated with allele-specific histone modification. Our study provides the first genome-wide map of allele-specific nucleosome occupancy in plants and suggests a mechanistic connection between chromatin organization and genomic imprinting.